The influence of mobile-assisted critical writing instructions on EFL learners' writing skill in language institutes - Zalani, Mahdi; Weisi, Hiwa; Yousofi, Nouroddin (Frontiers in Education, 2024)
This study examined the influence of mobile-assisted critical writing instructions on EFL learners' writing skill in language institutes. Ninety EFL learners who were studying English at three branches of a language institute in Iran took part in this research. Two equal groups as control and experimental were formed. As the pretest, a writing task was assigned to the groups which required them to write an argumentative report. The reports were the participants' personal analyses of the contents they had viewed on TV about an important political issue. After the pretest, the control group received instructions for critical writing in class without using Instagram. The treatment lasted for 12 weeks. During the treatment, the control group were asked to watch some TV channels devoted to news. The experimental group received instructions for critical writing in class and via Instagram. The treatment lasted for 12 weeks. The experimental group, who were all Instagram users, were asked to view some Instagram accounts belonging to famous news agencies. Additionally, an Instagram account was created by the teacher and they were asked to follow it for receiving instructions there. When the treatments ended, the posttest was administered. The control group were required to watch the TV channels and the experimental group were required to view the Instagram accounts to write an argumentative report about an important political issue. The reports were the participants' personal analyses of the contents they had viewed. Despite having nearly the same mean scores on the pretest, the two groups' mean scores on the posttest were different and the experimental group scored higher than the control group. Finally, fifteen members of the experimental group were interviewed. The focus of the interview was on the participants' suggestions and criticisms of the study. Overall, the experimental group had positive perceptions of the treatment. This study may have implications for teacher trainers, supervisors, teachers, and textbook writers.